2019
DOI: 10.1371/journal.pone.0225198
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted intervention for the prevention and management of musculoskeletal pain in nursing staff: Results of a cluster randomized controlled trial

Abstract: BackgroundNurses and nursing aides are at high risk of developing musculoskeletal pain (MSP). This study aimed to evaluate a multifaceted intervention to prevent and manage MSP in two hospitals.Material and methodsWe performed a two-armed cluster randomized controlled trial, with a late intervention control group. Clusters were independent hospital units with nursing staff as participants. The intervention comprised three evidence-based components: participatory ergonomics, health promotion activities and case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 50 publications
2
43
0
10
Order By: Relevance
“…The application of preventive programs and exercises among healthcare workers can reduce the incidence of musculoskeletal diseases, including LBP. Exercise once a week for 6 months combined with five sessions of back care counseling after working hours in real-life settings effectively reduced the intensity of LBP, work interference due to LBP, and fear of pain [19,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of preventive programs and exercises among healthcare workers can reduce the incidence of musculoskeletal diseases, including LBP. Exercise once a week for 6 months combined with five sessions of back care counseling after working hours in real-life settings effectively reduced the intensity of LBP, work interference due to LBP, and fear of pain [19,32].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of LBP among healthcare workers varies and in studies it ranges from 53% [12] to 92% in those involved in rotating shift work [16]. Long-term work, associated with forced body movements and postures, especially in nurses and technicians, lifting weights, with shift work, can enhance the occurrence of LBP, and thus negatively affect the work process, but also the quality of life of health workers [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The process evaluation was part of INTEVAL_Spain, a two-armed cluster randomized controlled trial with an intention-to-treat intervention. Detailed information on the content, methodology and evaluation of INTEVAL_Spain has been described previously [21][22][23]. Participation was voluntary and signed informed consent was obtained from all workers who agreed to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Components of the intervention were participatory ergonomics (primary prevention); healthy lifestyle promotion programme with Nordic walking, mindfulness, and healthy diet session (primary prevention); and tailored case management (secondary and tertiary prevention). The intervention effectiveness was evaluated in an intention-totreat cluster randomized controlled trial with the primary outcomes of reduction of MSP and sickness absence and lasted one year [21,22]. At one year follow-up, the effect evaluation showed that the intervention group had a signi cantly lower prevalence of MSP at the neck, shoulders and upper back compared to the control group [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation